Pengaruh Karakteristik Perusahaan Pada Pengungkapan Tanggung Jawab Sosial Perusahaan - Suprasto, Herkulanus Bambang; Haryanti, Angelia Putri Surya (Jurnal Ilmiah Akuntansi dan Bisnis, 2019)
This study aimed to provide empirical evidence on the effect of firm characteristics which include firm age, firm size, profitability, and board of commissioner size, on corporate social responsibility disclosure for firms listed on the Indonesia Stock Exchange. This research was conducted on firms listed on the Indonesia Stock Exchange with an observation period of 3 years, from 2015 to 2017. The sample of this study amounted to 52 firms with a total of 110 observations. A purposive sampling approach was used as the method of determining the sample used. The results showed that firm age and firm size had a positive effect on corporate social responsibility disclosure, while profitability and board of commissioner size cannot be proven to have no effect on corporate social responsibility disclosure. The results of this research also provide concrete evidence of the application and explanation of the mechanism of stakeholder theory as a grand theory of this study. Keywords : company characteristics, corporate social responsibility disclosure